Calidad de frutos de banano por efectos de fertilización para determinar la relación de severidad con la sigatoka negra mycosphaerella fijiensis morelet - Verdezoto Ochoa, Lenin Michael (2006)
It was studied the quality of banana tree fruits and the severity of the cream pulp chemically in an experiment designed to determine the influence of the nutrition and the severity of Mycosphaerella fijiensis. The used nutritional treatments were: N-150, 67, 50, 0; P-18.8, 25, 31.3, 0; K-150, 200, 250, 0; Mg-600, 800, 1000 and 0. The require-ments were calculated based on the analysis of floors and starting from this it was considered a less 25 %, minimum and more 25 %, settling down a relationship N/K 1:1; 1:3; 1:5 and the absolute witness. For this experiment a design complete blocks was used at random. The results indicated that the chemical components as soluble solids, pH, acidity titulable and relationship soluble solids and acidity titulable, have a changing effect for effect of the used nutritional relationships. It was determined that the relationship N/K/Mg 1:3 - 600/ have-year was the best option for a fertilization program in the place of the experiment. Also, the nutritional relationships had a significant effect on the reduction of the sigatoka. The severity of the cream pulp was diminished considerably when being used the relationship N/K/Mg 1:5-1 000.